2013
DOI: 10.1080/09695958.2013.874350
|View full text |Cite
|
Sign up to set email alerts
|

‘Shut up and bill’: workplace bullying challenges for the legal profession

Abstract: Keywords:Workplace bullying, workplace culture, billable hours, professional conduct, Australia "They want people who will shut up and bill" IntroductionThe context of modern work has changed significantly due to globalisation and increased competition (Noon et al., 2013). The impact of these changes can be felt at various levels, including: region, country, sector, industry and profession. The way in which work and employees are affected depends on how organisations, and professions, respond to the changes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…It is observed that WB if not managed well can have serious repercussions on the overall performance of the organization because a healthy, engaged, and happy workforce is not attainable (Khan & Khan, 2012). The ultimate aim of all organizations should be to create an attractive, sustainable, and accountable profession and safeguard the rights of employees to dignity and respect at workplace (Omari & Paull, 2013). As emphasized by Bac (2018) an organization with a performing workforce and exemplary internal compliance structure can meet its performance objectives only when it displays extremely low levels of harassment and WB.…”
Section: Interventions By Management Supervisors Self and Statementioning
confidence: 99%
“…It is observed that WB if not managed well can have serious repercussions on the overall performance of the organization because a healthy, engaged, and happy workforce is not attainable (Khan & Khan, 2012). The ultimate aim of all organizations should be to create an attractive, sustainable, and accountable profession and safeguard the rights of employees to dignity and respect at workplace (Omari & Paull, 2013). As emphasized by Bac (2018) an organization with a performing workforce and exemplary internal compliance structure can meet its performance objectives only when it displays extremely low levels of harassment and WB.…”
Section: Interventions By Management Supervisors Self and Statementioning
confidence: 99%
“…Brough and Biggs (2015b), for example, noted that assessments of job demands that are specifically focused on the work conducted by the respondent sample, demonstrate stronger associations compared to generic measures of job demands. This reasoning is supported by research which has included lawyer-specific assessments of job demands (e.g., interpersonal challenges, bullying, and excessive billing targets) and reported significant associations between these job demands and psychological strain (Omari & Paull, 2013;Tsai, Huang, & Chan, 2009). We acknowledge that such lawyer-specific assessments of job demands would have been valuable to include in the current research.…”
Section: Impact Upon Psychological Strain Work Engagement and Jobmentioning
confidence: 86%
“…The impact of occupational stress experienced by lawyers has only comparatively recently been reported. Similar to other criminal justice occupations, chronic occupational stress experienced by lawyers is associated with toxic work environments, work-life imbalance, and high levels of turnover (Brough, Brown, & Biggs, 2016;Omari & Paull, 2013;Seligman, Verkuil, & Kang, 2004). Marcus (2014) reported above average levels of suicide for Australian legal professionals, with an estimated 10% of lawyers regularly contemplating suicide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, there is an increasing, yet still small body of literature dedicated to documenting workplace incivility in the legal system in general (e.g., Cortina et al., 2002; Fischer, 2011; Miller et al., 2021). Many reasons have been suggested to explain the apparent decrease in civility within the legal system, including increased competition that has, in turn, exacerbated pressures to fulfill quotas and deliver on increasingly intense demands (Omari & Paull, 2014). Other given reasons include a continually growing number of attorneys leading to more competition for limited jobs; an increase in poorly‐ or under‐trained law graduates; an increase in demand by clients for zealous and combative attorneys; and a rise in the assumption that demonstrating civility will be perceived as a weakness (Fischer, 2011).…”
Section: Workplace Incivilitymentioning
confidence: 99%